P850 Measles virus immune status in a cohort of Spanish patients with inflammatory bowel disease. (25th January 2019) - Gómez-Outomuro, A; Castaño-García, A; Flórez-Díez, P; de Francisco, R; Rodriguez, M; Huerta-González, I; Pérez-Martínez, I; Martínez-González, S; Fernández-Prada, M; Suárez, A; Riestra, S
Abstract: Background: Despite vaccination against measles virus, outbreaks of this infection have been reported in western European countries. Little is known about measles virus serological status in adult patients with inflammatory bowel disease (IBD). On the other hand, few studies have analysed factors related to measles virus immune status. Our aim was to know the immune status against measles virus in a cohort of adult patients with IBD Methods: Single-centre study in IBD patients attended at an Spanish IBD unit between 2015 and 2018. At the diagnosis of IBD or at the first visit to the Unit, all patients were assessed for their serological status regarding measles virus by the determination of IgG antibodies. Factors related to measles virus immune status were analysed. Results: 430 patients were included, mean age 45.9 years, 51.9% male, 51.6% Crohn's disease, 44.7% ulcerative colitis and 3.7% unclassified colitis. In total, 36 patients (8.4%) were measles virus-IgG negative. There were no significant differences in percentage of seronegative patients according to gender ( p = 0.131), type of IBD ( p = 0.512) or treatment at the time of the testing [corticosteroids ( p = 0.560), immunomodulators ( p = 0.581) or biologics ( p = 0.784)]. Regarding age, seronegative patients were younger than seropositive (mean 31.8 years vs. 47.2 years; p < 0.001). Analysing by subgroups, we found differences between patients born before and after 1982 (measles vaccination start time in Spain); thus, 24.5% patients born after 1982 were seronegative vs. 2.8% among patients born before 1982 ( p < 0.001). We also found differences between patients born before and after 1991 (measles eradication time in our country) (18.4% seronegative among born after 1991 vs. 7.1% among born before, p < 0.001). In total, 16 of 36 patients (44.4%) were vaccinated. Of the remaining 20, 16 were not vaccinated because they were under immunosuppressive treatment, and one of them due to spontaneous seroconversion. There were no cases of measles. Conclusions: Immunosuppressive and biological therapy does not affect the immune status against measles virus in patients with IBD. Seronegative patients are younger, probably due to the immunity was only conferred by vaccination given the non-exposure of these patients to the wild virus. Half seronegative were not vaccinated because they were under immunosuppression. Therefore, we would like to emphasise the importance of knowing the immunological status of patients at the baseline visit in order to adjust the vaccination schedule before starting treatment.